Insidious Recurrent Biatrial Myxomas in Carney Complex with a Paucisymptomatic Spinal Melanotic Schwannoma: Advocacy for a Rigorous Multidisciplinary Follow-up to Prevent Dire Complications - Grandmougin, Daniel; Ehrlich, Tristan; Moussu, Teresa; Hubert, Maxime; Perin, Benjamin; Delolme, Maria Christina; Maureira, Juan-Pablo (Medical Science: Trends and Innovations Vol. 12, 2025)
Carney complex (CNC) is a rare autosomal syndrome resulting from either a dominant inheritance or a sporadic occurrence as a de novo genetic defect. CNC is characterized by a multiple neoplasia syndrome featuring myxomas of the heart, breast nipples, bone, skin, and mucosae and endocrine and nonendocrine, cutaneous, and neural tumors, as well as a variety of abnormal skin pigmentation and a predisposition to cancers such as thyroid, ovaries, pancreas, and liver. A 31-year-old female patient with a previous history of Carney complex and surgical resection for cardiac myxoma and bilateral adrenalectomy at 18 years old and 10 and 11 years old, respectively, was referred to our department with a diagnosis of recurrent Biatrial myxomas incidentally discovered on echography. A magnetic resonance imaging (MRI) confirmed the diagnosis of a tumor protruding into the left ventricle, and the patient underwent a surgical resection of a large left atrial mass and a small right-sided atrial tumor. The atrial mass was incidentally discovered by echography. Diagnosis of bilateral atrial myxomas was confirmed by histologic studies. Postoperative outcome was uneventful, and the patient was discharged on the 7th postoperative day. A few months later, she reported trivial clinical symptoms, suspecting a cervical radiculopathy. MRI confirmed the presence of a compressive cervical spinal cord tumoral mass at the C2-3 level, leading to a surgical excision of the tumor. Histology showed a spinal melanotic schwannoma. At 48-month follow-up, the patient is in good condition and regular echographic follow-up showed a 60% LVEF with neither recurrence of cardiac myxomas nor valve disease. A recent cerebral MRI revealed a normal pituitary gland without any tumoral patterns. This case highlights the risk of unexpected ubiquitary tumor locations and the importance of a rigorous transversal multidisciplinary follow-up to prevent severe complications in patients with Carney complex.